Characterization of a progressive neurodegenerative disease induced by a temperature-sensitive Moloney murine leukemia virus infection. - Bilello, J A (1986)
A progressive neurodegenerative disease occurred following infection of mice with a temperature-sensitive (ts) isolate of Moloney (Mo) murine leukemia virus (MuLV), ts Mo BA-1 MuLV. This NB-tropic ecotropic MuLV, which was ts for a late function, induced a syndrome of tremor, weakness of the hind limbs, and spasticity following infection of several strains of laboratory neonatal mice, including NFS, C3H/He, CBA, SJL, and BALB/c. The latent period of 8 to 16 weeks was considerably longer than that observed for the acute paralytic diseases observed following neonatal infection with other ts Mo-MuLV, rat-passaged Friend MuLV, and some wild mouse ecotropic MuLVs. Spongiform pathology without inflammation and degeneration of neurons devoid of budding virions occurred in the cerebellar grey matter, brain stem, and upper spinal cord; but lower spinal cord anterior horn cells were less obviously affected than in other MuLV-associated neuroparalytic syndromes. ts Mo BA-1 MuLV differed from other ts Mo-MuLV mutants that are capable of inducing a neuroparalytic syndrome in that while infected nervous system tissue contained high levels of MuLV p30 and gp70, no evidence of precursor accumulation or abnormal processing of MuLV p30 or gp70 could be demonstrated. The localization of virus within the nervous system suggests that direct neuronal infection may not be the etiologic mechanism in this MuLV-induced neurodegenerative disease.